ERF114/115/109 are essential for jasmonate-repressed non-canonical JAZ8 activity in JA signaling - Jiaxuan Sui; Qianlan Yin; Yiying Chen; Min Sun; Xianzheng Yuan; Zhaojun Ding; Xiangpei Kong (Cell Reports)
Summary: Jasmonate (JA), a key plant hormone, regulates various aspects of plant development and stress responses, primarily through the degradation of canonical jasmonate-ZIM domain (JAZ) proteins by the SCFCOI1 complex. While JAZ8, a non-canonical JAZ protein lacking the degron signal, has been shown to repress JA responses, the mechanism by which JA inhibits JAZ8 activity remains unclear. Here, we demonstrate that Arabidopsis ethylene response factor 114 (ERF114), ERF115, and ERF109 regulate JA signaling through interacting with JAZ8. This interaction disrupts the formation of the MYC2/3/4-JAZ8 and root hair defective 6 (RHD6)-JAZ8 complexes. We show that ERF114 positively regulates JA-induced transcriptional responses and that JA-promoted root hair growth is highly alleviated in erf114 mutants. Furthermore, the transcription of ERF114/115/109 is induced by JA in an MYC2-dependent manner, thus forming a positive feedback loop in JA signaling. Collectively, this study reveals a regulatory pathway in which ERF114/115/109 regulate JA signaling by targeting non-canonical JAZ proteins.